Ethics [videorecording] : what is right? - Kononovich, Lila; Garcia, Pablo; Films for the Humanities & Sciences (New Jersey : Film For The Humanities & Sciences, 2004)
In this program, Harvard University's Frances Kamm; Rutgers University's Larry Temkin; and Richard Sorabji, honorary fellow at Wolfson College, the University of Oxford, describe the three major categories of ethics: metaethics; applied ethics; and normative ethics, including virtue theory, divine command theory, utilitarian theory, and duty theory. Plato's Republic, Aristotle's Nicomachean Ethics, Kant's Grounding for the Metaphysics of Morals, and Mill's Utilitarianism are considered, along with the contributions of Epicurus, Hume, Bentham, Hegel, Marx, Nietzsche, John Rawls, and others
Title from title screen
Executive producers, Chris Scherer, Camila O'Donnell
DVD format
Keywords: Philosophy; Ethics; Philosophy -- History; Philosophy and society